Level of User Satisfaction with Hearing Aids and Environment: The International Outcome Inventory for Hearing Aids - Kozlowski, Lorena; Almeida, Gleide; Ribas, Angela (International Archives of Otorhinolaryngology, 2014)
Introduction The main function of hearing is to enable oral communication. Hearing loss impairs communication skills.Objective To evaluate the level of user satisfaction with hearing aids.Methods This is a cross-sectional group study comprising 108 subjects (56% men and 44% women). The average age of the subjects was 77 years. These subjects had been recently fitted with their hearing aids and showed sensorineural (90%) and mixed (10%) hearing loss as determined via the Questionnaire International Outcome Inventory for Hearing Aids Outcome Inventory (IOI-HA), which determined the benefit and satisfaction obtained by sound amplification.Results The hearing aids improved the quality of life of 52.78% of the patients, which was revealed by their high scores (mean = 27.3). The relationship of the user with the environment was significantly better (p < 0.001) than that of the user with the hearing aid.Conclusion IOI-HA is a simple and easy-to-use tool. Based on the results of this study, we can show a high degree of satisfaction with their hearing aids in the majority of the participants, which improved the quality of life.
Keywords: quality of life; hearing loss; consumer satisfaction